ACUTE DISSEMINATED ENCEPHALOMYELITIS IN CHICKEN POX - Arijit Sinha; Suvrendu Sankar Kar; Tirtha Pratim Purkait; Uttam Kumar Pandit (National Journal of Medical Research, 2016)
An 11 years old male was admitted with upper motor type of weakness of both lower limbs, retention of urine, impaired consciousness, tremor and convulsion on 11th day after vesicular eruption of chickenpox. He was investigated and treated. MRI Brain and Spine suggests encephalitis and myelitis. Other causes were excluded by relevant investigations. Patient was improved satisfactorily.